Corn productivity associated with inoculation with Azospirillum brasilense and different doses of nitrogen fertilization (Research, Society and Development, 2021)
Although chemical nitrogen fertilization is responsible for increasing corn crop productivity, its application is also responsible for increasing production costs and promoting a series of environmental risks. An alternative to this problem is biological nitrogen fixation. This work aims to evaluate the efficiency of inoculation with Azospirillum brasilense in the culture of corn associated with different doses of nitrogen fertilization in cover. The experiment was carried out in the experimental area of ​​UniEvangélica, with the treatments: control with 100% coverage; inoculation + 85% of coverage; inoculation + 85% coverage and application in coverage of A. brasilense; inoculation + 100% coverage. Morphological parameters and productivity were evaluated. The results were subjected to analysis of variance, and when there were significant differences, the Tukey means test (5% probability) was applied. The inoculation with A. brasilense and a 15% reduction in nitrogen fertilization in coverage, showed efficiency as a promoter of growth and vegetative development, significant effect on plant height and on the green and dry mass of the inflorescence. The inoculation with A. brasilense did not show significant results in maintaining productivity in the face of reduced nitrogen fertilization, with a 21% reduction in productivity.